2006
DOI: 10.1271/bbb.60130
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Methionine-Induced Hyperhomocysteinemia by Glycine and Serine in Rats

Abstract: The hyperhomocysteinemia induced by a dietary addition of 1% methionine was significantly suppressed by the concurrent addition of 1% glycine or 1.4% serine to the same degree. The methionine-induced increase in the hepatic concentration of methionine metabolites was significantly suppressed by glycine and serine, but the hepatic cystathionine -synthase activity was not enhanced by these amino acids. When the methioninesupplemented diet was changed to the methionine plus glycine or serine diet, the plasma homo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 30 publications
1
46
0
2
Order By: Relevance
“…Hence, in the present study, we used folate at a level of 20 mg/kg diet, which is considered to be the maximal dose within the nutritional range. On the other hand, in the present study, we used serine at a level of 2.5% according to our previous study showing that dietary supplementation with 2.5% serine completely suppressed methionine-induced hyperhomocysteinemia (31). The serine contents of 10C and 25S were estimated as 0.47 and 0.95%, respectively.…”
Section: Discussionmentioning
confidence: 97%
“…Hence, in the present study, we used folate at a level of 20 mg/kg diet, which is considered to be the maximal dose within the nutritional range. On the other hand, in the present study, we used serine at a level of 2.5% according to our previous study showing that dietary supplementation with 2.5% serine completely suppressed methionine-induced hyperhomocysteinemia (31). The serine contents of 10C and 25S were estimated as 0.47 and 0.95%, respectively.…”
Section: Discussionmentioning
confidence: 97%
“…4) The result that methionine-induced increases in the hepatic concentra- Each value is the mean AE SEM for 5 (25C), 10 (25CM), or 4 (other groups) rats. 25C, 25% casein diet; 25CM, 25C + 1% Lmethionine diet.…”
Section: )mentioning
confidence: 99%
“…Verhoef et al 3) have found that serine and cystine suppress the enhancement of plasma homocysteine concentration due to a single ingestion of a methionine-supplemented low-protein meal in humans. In addition, we found that dietary supplementation with glycine and with serine suppresses methionine-induced hyperhomocysteinemia in rats, 4) but little information is available on the effects of amino acids other than glycine, serine, and cystine on plasma homocysteine concentration.…”
mentioning
confidence: 98%
“…Ainda assim, autores apontam algumas controvérsias quanto aos clássicos estudos realizados por Mudd e Pole 36 e Mudd et al 37 e sugerem que a síntese de creatina pode não ser a maior responsável pelas reações de metiltransferases, apontando a biossíntese de fosfatidilcolina como importante determinante da demanda de metilação e consequentemente significante na produção de Hcy 56 . Além disso, estudos recentes têm demonstrado que outras importantes substân-cias podem modular o balanço de metilação e os ní-veis de Hcy como a betaína, glicina e serina 10,11 . Assim, mais estudos são necessários para quantificar a relativa contribuição dessas substâncias para as reações de metiltransferases, principalmente envolvendo a creatina.…”
Section: -Conclusões E Perspectivasunclassified
“…Ainda, alguns autores têm voltado sua atenção ao estado vitamínico 7,8 e polimorfismos genéticos relacionados à HHcy 9 . Recentemente, estudos têm buscado entender o balanço da demanda de metilação e os efeitos da modulação de tal balanço sobre o metabolismo da homocisteína 4,10,11 . Contudo, o objetivo desta revisão é discutir os efeitos da suplementação com creatina sobre os níveis de homocisteína, além do seu possível papel protetor contra a formação de espécies reativas de oxigênio, das interações e inter-relações da ingestão com a produção endógena de creatina.…”
Section: -Introduçãounclassified